رؤية وصفية للسلوك الاستهلاكي لدى الشباب - زويتي, سارة (جامعة الوادي - University of Eloued, 2017)
يعتبر الشباب اللبنة الأساسية لكل مجتمع الذي يحدد موضوعه وفق حاجات أفراده ونسق القيم السائد والجماعات المرجعية التي يتضمنها والمحددات الثقافية التي يعتنقها، ومن أهم فئات مستهدفة للسلوك الاستهلاكي هي هته الفئة، حيث يسعى السلوك الاستهلاكي للشباب الى التعرف على المنتج والسلع وتوجيه مواقفه اتجاه ورغباته الشرائية، وذلك من خلال تدعيم سلوكه والبحث عن التغير والأفضل وحب الاستطلاع والاكتشاف من خلال الوسائل التي تؤثر في السلوك من الأسرة، إلى جماعة الرفاق، إلى الاتصال التسويقي...الخ. وما ثم تبرز أهمية هدا التأثير على المستهلك وغرس فيه روح التعود والتذكير من خلال العروض وسائل الإعلام والعمل على التأثير في سلوكه من اجل استهلاك سلعة أو منتوج ما والعمل كذلك على إقناعه وجذبه نحو منتوج معين. فبإثارة الدافع الاستهلاكي للفرد، ويعمل على تنمية سلوكه من خلال تعوده على ذلك وإشباع حاجياته ورغباته، كما يعمل على التأثير فيه والتعلق به. وعليه يمكن طرح التساؤل التالي: كيف يمكن إثارة السلوك الاستهلاكي لدى الشباب ؟ وما هي العوامل المتحكمة في السلوك الاستهلاكي؟ Youth is the bedrock of every community that identifies its subject according to the needs of its members and the prevailing values theme and reference groups and cultural determinants espouses, one of the main target groups Consumer behaviour are those category, as consumer behavior for young people to learn about the product and goods and directing his direction and his wishes, through strengthening its behaviour and look for change And better yet, curiosity and discovery through affecting the behavior of the family, peer group, to your catalog. Etc. And then highlight the importance of this impact on consumer and inculcate the spirit of habituation and remembered through presentations and media work to influence his behavior for the consumption of a commodity or a product and work further on persuading him Lured towards any particular product. They raise impulse per capita consumption, and is working on the development of behavior through his familiarity with and satisfy his needs and desires, and to influence it and hung up. It could ask the following question: How do you raise consumer behaviour among young people? What is the controlling factor in consumer behavior?
مقال في مجلة السراج في التربية وقضايا المجتمع بجامعة الوادي
Keywords: السلوك الاستهلاكي، الشباب; consumer behaviour, youth